2011
DOI: 10.1111/j.1468-3083.2010.03743.x
|View full text |Cite
|
Sign up to set email alerts
|

Stromal expression of cathepsin K in squamous cell carcinoma

Abstract: Cathepsin K-positive stromal fibroblasts may play a crucial role in SCC progression by promoting extracellular matrix degradation, thereby facilitating SCC growth and invasion into surrounding tissue and vasculature. CTSK inhibitors may be a potential novel therapeutic option to decrease SCC progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 16 publications
3
28
1
1
Order By: Relevance
“…The human cysteine cathepsin family includes 11 members which share a conserved activated site, and they primarily function as intracellular proteases mediating terminal nonspecific bulk proteolysis in the acidic environment of lysosomes via phagocytosis [18]. CTSK degrades components of the ECM and basement membranes, and is overexpressed in stromal Fbs at the invasive front of various malignant tumors [9][10][11][12][13][14]19,20]. However, the regulatory mechanism and implication of fibroblastic CTSK expression remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human cysteine cathepsin family includes 11 members which share a conserved activated site, and they primarily function as intracellular proteases mediating terminal nonspecific bulk proteolysis in the acidic environment of lysosomes via phagocytosis [18]. CTSK degrades components of the ECM and basement membranes, and is overexpressed in stromal Fbs at the invasive front of various malignant tumors [9][10][11][12][13][14]19,20]. However, the regulatory mechanism and implication of fibroblastic CTSK expression remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CTSK has a uniquely high potency to degrade a wide range of collagens at multiple sites within the triple helix as well as at extra-helical regions [8]. Previous reports have shown that CTSK expression is implicated in the invasive growth of primary tumors in prostate, breast, thyroid and cutaneous squamous cell carcinoma (SCC), where CTSK overexpression by stromal Fbs is associated with an increased invasive potential [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Strong cathepsin K expression was also observed in primary melanomas and melanoma metastases (Quintanilla -Dieck et al, 2008 ). In squamous cell carcinoma, expression of cathepsin K by stromal fibroblasts was stimulated by the tumor cells via secretion of interleukin-1 α and correlated with the invasiveness of the tumor Yan et al , 2011 ).…”
Section: Cathepsin K In Cancermentioning
confidence: 94%
“…It has an important role in many other tissues, as well [13], [14], [18], [19]. In general, the expression of cathepsin K in normal tissue seems to be associated with the process of extracellular matrix turnover.…”
Section: Introductionmentioning
confidence: 99%